Analisis Identifikasi dan Guilt pada Teori Dramatisme Kenneth Burke dalam Film “They Live 1988” - Achmad Sigit Syarifuddin; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
According to Burke, Dramatism means humans can learn and understand motives in all human interactions through symbols. Burke sees that the motives behind people's actions are essential for analyzing and finding out why people do and say what they do. Apart from the dramatic Pentad which is one of the important concepts in dramatism, there are identification, guilt and ratio. There are six ways of identification, formal patterns, framing, ambiguous symbols, mystification, and scapegoats. There are two forms of guilt, namely mortification and victimage. There are two forms of guilt, mortification and labeling the enemy or the victim of victimage. This study aims to analyze existing data to present the basic findings of dramatism theory, identification and guilt in the film